Variability in Hip Characters in Rosa Species - T Janakiram (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2008)
The reddish 'fruit' of rose is commonly known as its hip. Rose hips are formed when the tip of a rose stem swells up after a flower has faded. Species roses, shrub roses, ramblers and other roses that are "close to nature" (R. gallica, R. rugosa) are the most likely to have noticeable hips. Twenty three rose species were evaluated for hip characters. Rose hips were very variable among the species. Average hip length and diameter varies between 0.5 to 2.8 cm and 0.1 to 2.7 cm, respectively. Hip shape viz., sub-globose, urn-shaped, ellipsoid and spindle-shaped were observed among the species. The range for number of hips was found to be 5 to 45 per cluster. Rosa rugosa recorded larger hip size. Majority of the species showed orange and deep red hip color. R. moyesii (blue-green foliage and bright to orange hips), R. glauca (bright scarlet hips), R. pimpinellifolia (tiny, red-black hips) with attractive hips having ornamental value can be utilized in landscaping and for garden purposes.